(untitled) (Research, Society and Development, 2021)
Objective: To report the experience of medical students in the extension project “Building a link between the university and the community: deployment of the Alegromicina group in the city of Toledo - Paraná.” Methodology: This is a descriptive-exploratory study with a qualitative approach, an experience report about an extension project at the Federal University of Paraná in which visits were made to patients admitted to a hospital, in the clinical and pediatric wings, and a hemodialysis clinic in Toledo, Paraná, between the years 2017 to 2020. The students dressed like clowns to carry out visits that advocated dialogue, musical approaches, activities in the hospital playroom or even in the beds, adapting to the context and audience approached. Result: The actions carried out by the project reached around 800 people per year and, by encouraging joy and relief, they reduced suffering in the context of emotional fragility experienced by patients, companions and even health professionals. Thus, the negative experience related to hospitalization was also reduced. The ability to perceive the patient beyond his illness was one of the positive aspects noticed by the students who were able to experience humanization and comprehensive care. Conclusion: The Alegromicina project brought benefits to patients, companions, health professionals and students participating in the project by promoting the humanization of the hospital environment The deployment of programs that use the role of the clown and the performance of playful activities help in the prognosis of diseases and make the hospitalization experience less traumatic.